Effectiveness of an early reading intervention in a semi-transparent orthography: A group randomised controlled trial. (December 2018) - Solheim, Oddny Judith; Frijters, Jan C.; Lundetræ, Kjersti; Uppstad, Per Henning
Abstract: This study reports on the effectiveness of an early reading intervention, based on current research on early reading acquisition, and aligned to Norwegian orthography. Thirteen schools were randomly assigned to one of two interventions or a control condition. First grade students (n = 744) were screened at school entry, and children at risk of reading difficulties (n = 140) were identified. At-risk students in schools allocated for intervention received comprehensive teacher-led instruction also containing an individually-delivered computer component. The only difference between the two interventions was whether the computer application had adaptive learning features. Both interventions had significant impact on reading and spelling with no significant difference between the two different intervention conditions. Findings indicate that Norwegian children identified to be at-risk at school entry can profit from intensive intervention that combines training in letter knowledge with explicit instruction in phonetic decoding and word recognition, free spelling, connected text reading and shared reading. Highlights: A multi-component reading intervention for students at risk for RD is proposed. The proposed intervention is evaluated in a sample of Norwegian first graders. Intervention students outperform controls on reading and spelling after treatment. Adaptive and fixed computer applications are evaluated and found equally effective. At-risk children receiving intervention showed parallel growth with not-at-risk.